2017
DOI: 10.1097/inf.0000000000001453
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypoxia and Tachypnea Among Adolescents With Vertically-acquired HIV in Nairobi

Abstract: Background Chronic lung diseases are increasingly recognized complications of vertically-acquired HIV among adolescents in sub-Saharan Africa and may manifest with hypoxia or tachypnea. We sought to determine the prevalence of and risk factors for hypoxia and tachypnea among adolescents with vertically-acquired HIV in Nairobi, Kenya. Methods We performed a cross-sectional analysis of 258 adolescents with vertically-acquired HIV who were initiating care at the Coptic Hope Center for Infectious Diseases. Adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Chronic cough and sputum production were reported by 21–60% and breathlessness by 12–18%, but wheezing was uncommon [8*,10*,11*,12*,13*,14*,15*]. The prevalence of tachypnoea is difficult to quantify as definitions vary between studies, but elevated respiratory rates are common [8*,9*,10*,11*, 15*]. Hypoxia after sub-maximal exercise was a striking finding among 12–38% [10*,11*,12*,13*,15*,16*].…”
Section: Spectrum Of Chronic Lung Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Chronic cough and sputum production were reported by 21–60% and breathlessness by 12–18%, but wheezing was uncommon [8*,10*,11*,12*,13*,14*,15*]. The prevalence of tachypnoea is difficult to quantify as definitions vary between studies, but elevated respiratory rates are common [8*,9*,10*,11*, 15*]. Hypoxia after sub-maximal exercise was a striking finding among 12–38% [10*,11*,12*,13*,15*,16*].…”
Section: Spectrum Of Chronic Lung Diseasementioning
confidence: 99%
“…Additionally, in contrast with high-income settings where the majority of HIV-infected children initiate ART in infancy, a substantial proportion of children are diagnosed with HIV and initiate ART in later childhood. Among adolescents with delayed diagnosis of perinatally-acquired HIV in sub-Saharan Africa, older age and low FEV 1 and FVC z -scores appear to be associated [9*,11*,13*,15*]. This might reflect accumulation of insults over time and survivor bias.…”
Section: Risk Factors For Hiv-associated Chronic Lung Disease Among Amentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies from sub-Saharan Africa have reported a high prevalence of chronic lung disease, even among older children receiving ART [ 5–7 ]. The typical clinical picture is of a chronic, usually nonproductive, cough, hypoxia, tachypnea, reduced exercise tolerance and decreased lung function, and “nonspecific” chest radiographic abnormalities [ 8 ]. Plain chest radiography, despite its ready availability, is insensitive, and terminology used to define abnormalities often inconsistent.…”
mentioning
confidence: 99%